An ocean full of BARRELS: Barrels XXVI meeting report. (June 2014) - Chu, Philip; Chen, Chia-Chien; Brumberg, Joshua C.
Abstract The 26th annual Barrels meeting was convened on the campus of the University of California San Diego, not far from the shores of the Pacific Ocean. The meeting focused on three main themes: the structure and function of the thalamic reticular nucleus, the neurovasculature system and its role in brain metabolism, and the origins and functions of cortical GABAergic interneurons. In addition to the major themes, there were short talks, a data blitz, and a poster session which highlighted the diversity and quality of the research ongoing in the rodent whisker-to-barrel system.